Analisis Daya Tarik Atmosfer Instagramable untuk Menarik Minat Kunjung Kembali Wisatawan di Blitar Park - Denok Wahyudi Setyo Rahayu; Aqnes Dwi Sakti Hamidah (Jurnal Simki Economic, 2024)
The use of social media such as Instagram is very popular. Instagram is a forum for users to display their user activities in the form of photos or videos. Uploading photos and videos is a common thing for Instagram account owners. The aim of the research is to determine the attractiveness of an instagrammable atmosphere to attract tourists to come back to Blitar Park. The variables used in the research are the interior and exterior of Blitar Park as independent variables, while tourist return interest is the dependent variable. The population is visitors to Blitar Park. The sampling technique used Accidental Sampling provided that the respondent had visited Taman Blitar and was aged 17 years or over with a total sample of 116 respondents. The data analysis method applied involves applying validity and reliability tests, classical assumption tests, including normality tests, multicollinearity tests, and heteroscedasticity tests. Apart from that, it also involves multiple linear regression analysis and analysis of the coefficient of determination. The research results show that Blitar Park's internal and external variables influence tourists' interest in visiting again, both partially and simultaneously.